2014
DOI: 10.1371/journal.pone.0089641
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Receptors Expressed in Drosophila Mushroom Bodies Differentially Modulate Larval Locomotion

Abstract: Drosophila melanogaster has been successfully used as a simple model to study the cellular and molecular mechanisms underlying behaviors, including the generation of motor programs. Thus, it has been shown that, as in vertebrates, CNS biogenic amines (BA) including serotonin (5HT) participate in motor control in Drosophila. Several evidence show that BA systems innervate an important association area in the insect brain previously associated to the planning and/or execution of motor programs, the Mushroom Bodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 62 publications
(65 reference statements)
4
57
0
Order By: Relevance
“…We were also able to identify the neurotransmitter receptors dominant in each of these cell types (Figure 4A). While we confirmed that KCs express DopR, DopR2, OAMB, and 5-HT1A and 1B receptors (Han et al, 1998; Han et al, 1996; Qin et al, 2012; Silva et al, 2014; Yuan et al, 2006), we discovered that these receptors are also expressed in MBONs, but at lower levels than in the KCs (see also Figure S5). This indicates that both the KCs and MBONs have the ability to respond to the dopamine signal (carrying information about punishment or reward) innervating each compartment of the MB lobes.…”
Section: Resultssupporting
confidence: 63%
“…We were also able to identify the neurotransmitter receptors dominant in each of these cell types (Figure 4A). While we confirmed that KCs express DopR, DopR2, OAMB, and 5-HT1A and 1B receptors (Han et al, 1998; Han et al, 1996; Qin et al, 2012; Silva et al, 2014; Yuan et al, 2006), we discovered that these receptors are also expressed in MBONs, but at lower levels than in the KCs (see also Figure S5). This indicates that both the KCs and MBONs have the ability to respond to the dopamine signal (carrying information about punishment or reward) innervating each compartment of the MB lobes.…”
Section: Resultssupporting
confidence: 63%
“…Animals expressing RNAi for d5-HT 1B , d5-HT 2 or d5-HT 7 , but not d5-HT 1A in MBs showed increased motor behavior. Thus, all three d5-HTRs expressed in MBs decrease locomotor activity in fly larvae, although the activation of d5-HT 1B in other CNS regions may counteract its own action in the MBs [81]. Similarly, it has been reported in the leech that 5-HT activates the locomotor network at the nerve cord level, but inhibits locomotion at the head brain level [61].…”
Section: Motor Activity and Locomotionmentioning
confidence: 74%
“…CNS-located serotonin neurons provide a tissue basis for additional roles for White other than in controlling eye color in pigment cells. These neurons release serotonin (5HT), which acts as a neuromodulator involved in locomotor behavior, circadian entrainment and place memory (YUAN et al 2005;SITARAMAN et al 2008;NALL and SEHGAL 2014;OKUSAWA et al 2014;SILVA et al 2014). Recovery from anoxia includes the restoration of 5HT vesicular stores that would be excessively released during anoxic coma (HANSEN 1985).…”
Section: Multiple Roles Of White Proteinmentioning
confidence: 99%